Kajian Pengurangan Getaran Tanah (Ground vibration) Pada Peledakan Overburden Tambang Batubara Di PT. Artamulia TataPratama Site Tanjung Belit Provinsi Jambi - Ahmad Ridho Permana; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2019)
Abstrak. PT. Artamulia Tatapratama generally consists of two main materials namely claystone and sandstone with the value of the test results of the UCS test averaging above 20 MPa, which belongs to the hard rock category. Therefore, blasting activities were carried out in an effort to provide more effective and efficient overburden constituent materials. Blasting activities carried out in addition to paying attention to the production target must also be taken into account the impact of the blasting it self, especially in terms of ground vibration which can cause negative effects on the surrounding area, if it exceeds the established standards. Recording data of ground vibration measurements on the Vibracord DX series devices carried out by PT. Artamulia Tatapratama showed that the maximum value of soil vibration level produced reached            2.98 mm / second, while the threshold threshold value agreed upon by the local government together with the surrounding community, and PT. Artamulia Tatapratama which is equal to      1.4 mm / second. Whereas according to the Indonesian National Standard (SNI) the maximum value of vibration blasting is 3 mm / sec (based on the condition of the building around the blasting area) Keywords: Seismic wive, Blasting, Peak Particle Velocity, scale distance, ground vibration